Assessment of Well Water Quality for Drinking Purposes Within Selevania District, Zakho City, Kurdistan Region / Iraq - Al- Barwary, Musher R. A. (Science Journal of University of Zakho, 2021)
The world’s major sources of drinking water are groundwater particularly wells water. In the present study, the quality of the wells in the 10 villages nearby the city of Zakho were selected for investigation and their suitability for drinking purposes. All the well water samples were analyzed for 11 chemical and physical analysis including dissolved oxygen, total hardness, chloride, total dissolved solids, electrical conductivity, pH, sulfate, and four heavy metals, such as Cu, Fe, Pb, and Zn using standard methods. The results showed that the value of heavy metals in well water samples were in these ranges: Zn (0.027± 0.004 to 0.005 ± 0.007) mg/L; Fe (0.0109 ± 0.035 to 0.183 ± 0.061) mg/L; Cu (0.001 ± 0.022 to 0.025 ± 0.023) mg/L; Pb (0.045 ± 0.015 to 0.069 ± 0.096) mg/L. The range of physical and chemical parameters were; pH (7.1 to 8.3), EC (411 to1579 µS/cm), TDS (263 to 1010 mg/L), Total Alkalinity (287 to 584 mg/L), Total hardness (176 to 848 mg/L), Chloride (11.6 to 56.9 mg/L), calcium (80 to 673 mg/L), dissolved oxygen (6.1 to 8.7 mg/L), sulfate (10.3 to 42.5 mg/L) and temperature (17.0 to 23.4°C). The results were compared with international standards and showed that the mean values of total hardness and TDS in locations betas, Bezehe and Dolla are ranged from (827.13 ± 5.330), (544.25 ±3.178) ,(782.63 ± 3.257), (930.38 ± 3.545), (675.75± 3.639) ,( 996.25 ± 3.245) mg/L respectively, were found to be higher than WHO water standards, and unsuitable for drinking use. The results have proven the presence of heavy metal as especially lead, Zn, Cu, and Fe have been containing in the study area. Other parameters were within (WHO) drinking water standards. In conclusion, the other sites of well water sources of the Selevania region are suitable for drinking purposes.